2020
DOI: 10.1007/s00784-020-03226-3
|View full text |Cite
|
Sign up to set email alerts
|

Disease activity, morning stiffness and missing teeth are associated with oral health-related quality of life in individuals with rheumatoid arthritis

Abstract: Objectives The aim of this cross-sectional study was to assess oral health-related quality of life (OHRQoL) in patients with rheumatoid arthritis (RA) and its relation to specific RA characteristics. Material and methods Within the oral examination, the need for dental (carious teeth showing cavitation) and periodontal treatment (presence of a probing depth ≥ 3.5 mm) and the number of missing teeth (M-T) were recorded. OHRQoL was assessed with the German short version of the Oral Health Impact Profile (OHIP G1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 32 publications
(47 reference statements)
4
20
0
1
Order By: Relevance
“…Therefore, differences in OHRQoL between the different entities might be explainable by the different disease-related burden and its potential impact on psychosocial situation. This assumption is supported by a previous study showing disease activity of RA to be correlated with psychosocial impact within OHRQoL (Schmalz et al, 2020).…”
Section: Comparison With International Literaturesupporting
confidence: 75%
See 4 more Smart Citations
“…Therefore, differences in OHRQoL between the different entities might be explainable by the different disease-related burden and its potential impact on psychosocial situation. This assumption is supported by a previous study showing disease activity of RA to be correlated with psychosocial impact within OHRQoL (Schmalz et al, 2020).…”
Section: Comparison With International Literaturesupporting
confidence: 75%
“…The OHIP G14 sum score in the current study lied between the scores of two previous German studies, which showed values of 5.4 and 7.7, respectively (Mühlberg et al, 2017;Schmalz et al, 2020).…”
Section: Comparison With International Literaturesupporting
confidence: 74%
See 3 more Smart Citations